Green aspects of photocatalysts during corona pandemic: a promising role for the deactivation of COVID-19 virus. Issue 22 (6th May 2022) - Kumar, Abhinandan; Soni, Vatika; Singh, Pardeep; Parwaz Khan, Aftab Aslam; Nazim, Mohammed; Mohapatra, Satyabrata; Saini, Vipin; Raizada, Pankaj; Hussain, Chaudhery Mustansar; Shaban, Mohamed; Marwani, Hadi M.; Asiri, Abdullah M.
Abstract : Photocatalysts are green, eco-friendly, clean and sustainable and could be a solution to combat COVID-19 because of potential features of various types of metal oxides against viral inactivation via the generation of reactive oxidative species. Abstract : The selection of a facile, eco-friendly, and effective methodology is the need of the hour for efficient curing of the COVID-19 virus in air, water, and many food products. Recently, semiconductor-based photocatalytic methodologies have provided promising, green, and sustainable approaches to battle against viral activation via the oxidative capabilities of various photocatalysts with excellent performance under moderate conditions and negligible by-products generation as well. Considering this, recent advances in photocatalysis for combating the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are inclusively highlighted. Starting from the origin to the introduction of the coronavirus, the significant potential of photocatalysis against viral prevention and -disinfection is discussed thoroughly. Various photocatalytic material-based systems including metal-oxides, metal-free and advanced 2D materials (MXenes, MOFs and COFs) are systematically examined to understand the mechanistic insights of virus-disinfection in the human body to fight against COVID-19 disease. Also, a roadmap toward sustainable solutions for ongoing COVID-19 contagion is also presented. Finally, the challenges in this field and future perspectives are comprehensively discussed involving the bottlenecks of current photocatalytic systems along with potential recommendations to deal with upcoming pandemic situations in the future.